Effectiveness of Tamarillo Skin Extract (Solanum betaceum Cav.) with Sealer Combination in Inhibiting Growth of Enterococcus faecalis - E.Y, Siregar; Novelya; Susanto C (Biomedical Journal of Indonesia, 2021)
Introduction : Caries is a growth medium for pathogenic micro-organisms an inflammatory process can occur which can cause damage to the tooth pulp. Enterococcus faecalis one of the Gram-positive facultative anaerobes which causes failure after endodontic treatment. In the field of dentistry, herbal ingredients can be used as alternative medicinal ingredients because the ingredients is tamarillo skin which contains flavonoids, terpenoids, saponins and phenol compounds. In addition to herbal alternatives, endodontic filling also uses ingredients that have antibacterial potential that can kill and prevent reproduction in the root canals, one of which is the zinc oxide eugenol sealer which is usually applied together with gutta percha. Research objective: to determine the effectiveness of the extract of tamarillo (Solanum betaccum Cav.) skin sealer combination in inhibiting the growth of Enterococcus faecalis. Method: The research was conducted in an experimental laboratory post test only control group design. Results : a sealer made from zinc oxide-eugenol had the largest diameter compared to the combination group of 100%, 75%, 50%, 25% tamarillo skin extract with sealer, and aquadest. Based on the One Way Anova test, there was a significant difference in the mean diameter of the inhibition zone (p <0.05) and the Post Hoc LSD analysis test showed that the sealer was the best group to kill the Enterococcus faecalis bacteria. Conclusion : sealers have a good effect on inhibiting Enterococcus faecalis bacteria as a cause of failure in endodontic treatment.